Students' Learning Difficulties and Self-Efficacy in Mathematics Learning: An Analysis of the Relationship Between Cognitive and Affective Aspects - Syarif, Muqsitulqadri; Murniati. M; Mutiara Ramadhani; Sriyanti Mustafa; Hadmal (Edumaspul: Jurnal Pendidikan, 2026)
This study aimed to describe students' learning difficulties and explore their relationship with students' self-efficacy in mathematics learning among eleventh-grade students at SMAN 4 Parepare. A descriptive qualitative approach was employed, involving 25 students as the research participants. Data were collected using a student profiling questionnaire developed based on indicators of learning difficulties and self-efficacy and were analyzed descriptively using mean scores. The findings revealed that students' learning difficulties were categorized as moderate, with mean scores of 2.69 for logical thinking and problem-solving skills and 3.06 for conceptual understanding. In contrast, students' self-efficacy was categorized as low, with a mean score of 2.05. These findings indicate a discrepancy between the cognitive and affective domains, where relatively adequate conceptual understanding is not accompanied by strong self-efficacy. Difficulties in logical thinking and problem-solving appear to reduce students' confidence in their ability to perform mathematical tasks, which subsequently limits their participation in classroom learning. It can therefore be concluded that learning difficulties influence not only students' cognitive development but also their affective domain, particularly their self-efficacy. These findings suggest that mathematics instruction should focus not only on strengthening conceptual understanding but also on enhancing students' self-efficacy to encourage more active, confident, and meaningful learning.